Penanaman Karakter Pencegahan Penyakit Seks Menular Untuk Memberikan Edukasi Peserta Didik Di MTs Takhassus Al-Muhibbin - Astina, Chairani; Haryadi, Arif Puji; Wicaksono, Faris Sulthon; Maulina, Berlian Rahma; Yusup, Faisal Said; Allaudin Sulton, Fatih Allaudin Sulton; Hasanah, Arum Latifatul; Destiana; Khoirunnisa’, Nadya; Azizah, Ani Fatun; Fatikhah, Fina Rakhmania Fatikhah; Annisa’, Mytha; Febrianto, Hendi (Institut Agama Islam Hamzanwadi NW Pancor, 2023)
The development of an increasingly modern era and the flow of globalization in the world has increasingly caused various sectors and fields to experience adjustments. The impact of globalization and the development of the times is felt by people all over the world. They experience adjustments to the impacts arising from this. The impact can be either positive or negative. These various impacts are felt by humans, especially the younger generation, especially in the Indonesian region. Various problems arise and have fatal consequences if not handled early, they will even damage and harm future generations of youth. The emergence of free sex and juvenile delinquency will have a negative impact on the mental and physical health of the younger generation. Sexually transmitted diseases have mushroomed in various regions, including Wonosobo district. The need for education and instilling character to prevent sexually transmitted diseases is very necessary so that the younger generation does not fall into negative things that damage their morals and mentality. In addition to providing prevention, this activity will provide appropriate steps to provide experience and motivation so that incidents related to sexually transmitted diseases can be resolved and not recur.